Chinese University Students’ Attitudes and Perceptions in Learning English Using ChatGPT - Binghan Liu (Ilmu Inovasi Nusantara, 2023)
Since its release into the public domain, the generative AI tool - ChatGPT has arisen wide attention by its sophisticated capacity to carry out complex tasks. Many educators have researched the advanced tool in offering potential benefits for language teaching and learning. This research is designed for assessing Chinese university students’ attitudes towards using ChatGPT to improve their English learning and their perceptions regarding the advantages and disadvantages of ChatGPT. In this study, data were collected from 109 undergraduate Chinese students, using a questionnaire consisting of 5-point Likert scale questions. The findings of the study show that the students believe ChatGPT is an effective tool to support them in learning English but information security should be taken into further consideration. Policymakers, technology experts, researchers, and educators could work together on how ChatGPT and other evolving generative AI tools could be used safely and effectively in English teaching and learning